Synthesis, physical and electroluminescence properties of 3,6-dipyrenylcarbazole end capped oligofluorenes - Sangchart,T. (Royal Society of Chemistry, 2015)
© The Royal Society of Chemistry 2015. A series of oligofluorenes bearing two 3,6-dipyrenylcarbazole units as the terminal substituents, namely BPCFn (n = 1-3), were successfully synthesized and characterized as non-doped hole-transporting blue emitters. These molecules showed strong blue emission with good solubility, and thermally stable amorphous and excellent film-forming properties. OLEDs using these materials as the emissive layers were fabricated by a simple solution spin-coating process. The blue OLED with excellent device performance (brightness of 6085 cd m-2, luminance efficiency of 4.13 cd A-1 and turn-on voltage of 3.4 V) was attained from BPCF3.